Phytoremediation of Metals in Industrial Sludge by Cyperus Kyllingia-Rasiga, Asystassia Intrusa and Scindapsus Pictus Var Argyaeus Plant Species - Abdul Latiff, Ab. Aziz; Abd. Karim, Ahmad Tarmizi; Ahmad, Ahmad Shukri; Ridzuan, Mohd Baharudin; Yung-Tse, Hung (International Journal of Integrated Engineering, 2012)
Laboratory studies have shown phytoremediation is a feasible method for remediating sludgecontaminated with heavy metals. This research focused on the ability of plants to hydroponically treat digestedindustrial sludge contaminated with aluminium (Al), cadmium (Cd), chromium (Cr), copper (Cu), iron (Fe), lead(Pb), nickel (Ni), manganese (Mn) and zinc (Zn). The sludge used in the study was obtained from the wastewatertreatment lagoon of a textile factory. Three species were used in the phytoremediation process. They were CyperusKyllingia-Rasiga, Asystassia Intrusa and Scindapsus Pictus Var Argyaeus. These species were planted inhydroponic pots placed under a transparent roof to allow natural light. In the first batch, pots containing 2 seedlingsof each plant were applied with 9.81 mg, 12.83 mg, 15.85 mg, 18.87 mg and 21.9 mg digested dried industrialsludge. In the second batch, the pots planted with 1, 2, 3, 4 and 5 seedlings and were applied with the same amountof 21.9 mg of digested industrial sludge each. The pH and electrical conductance (EC) of hydroponic solution weremonitored in this phytoremediation processes. The results showed that the absorption of heavy metals byAsystassia Intrusa was in the order of Mn > Al > Cu > Fe > Ni > Zn > Cd > Pb > Cr, with medium pH and EC of6.90 ± 0.73 and 2.47 ± 1.96 μS/cm respectively . The absorption of heavy metals by Cyperus Kyllingia-Rasigawas in the order of Mn > Cu > Ni > Cr > Pb > Zn > Fe > Al > Cd at medium pH 6.87 ± 0.71 and EC 2.72 ± 1.85μS/cm and the absorption by Scindapsus Pictus Var Argyaeus was in the order of Cu > Ni > Mn > Pb > Zn > Cr >Cd > Al > Fe at neutral pH and the EC 2.72 ± 1.71 μS/cm. From the study it was concluded that the plant speciesused were able to significantly absorb the metals present in industrial sludge.